Investigating the Reliability of Shore Hardness in the Design of Procedural Task Trainers - Kyleigh Kriener; Kate Sinclair; Grant Robison; Raushan Lala; Hayley Finley; William Jase Richardson; Mark J. Midwinter (Bioengineering)
The haptic fidelity of biomimetic materials used in the design of procedural task trainers is of growing interest to the medical community. Shore hardness has been proposed as a method for assessing tissue biomechanics and replicating the results as a way to increase the fidelity of biomimetics to tissues. However, there is limited research on the reliability of human tissue measurements using Shore scales. Using human tissues (internal carotid artery [ICA], internal jugular vein [IJV], vagus nerve [VN], sternocleidomastoid muscle [SCM], and overlying skin [skin]), this study evaluates (1) the inter-rater reliability of Shore hardness measurements, (2) examines the relationship between tissue thickness and hardness, and (3) investigates the impact of a measurement method (freehand vs. durometer stand). Preserved tissues, specifically a liver and components of the anterior triangle of the neck, were extracted from cadavers and measured by three independent raters using digital Shore durometers. Testing revealed that although Shore A demonstrated better inter-rater reliability compared to Shore OO, both scales exhibited poor-to-moderate reliability. ICC values for Shore A ranged from 0.21 to 0.80 and were statistically significant (p < 0.05) for all tissue types except the SCM. In contrast, Shore OO demonstrated poorer reliability, with ICC values ranging from 0.00 to 0.41. The ICC values were only significant for the ICA, IJV, and VN (p < 0.05). An inverse correlation between tissue thickness and hardness on the Shore A scale was found for all tissues and was significant (p < 0.05) for ICA, VN, and skin. There were mixed results for the correlation between tissue thickness and hardness on the Shore OO scale (−0.06–0.92), and only IJV had a statistically significant correlation (p < 0.05). Finally, the median hardness values on the Shore OO scale were significantly greater when measured using a durometer stand vs. freehand (Z = 4.78, p < 0.05). In summary, when using appropriate standards and addressing the challenges of tissue thickness and variability in freehand measures, Shore hardness has the potential to be used by clinicians in the clinical setting and in the selection of biomimetic materials in the design of task trainers.